1997
DOI: 10.1136/adc.76.5.421
|View full text |Cite
|
Sign up to set email alerts
|

Developmental quotient at 24 months and fatty acid composition of diet in early infancy: a follow up study

Abstract: Aim-A follow up study of developmental quotient (DQ) at 24 months of toddlers whose diets in early infancy diVered in fatty acid composition, and in whom an association between diet and DQ was observed at 4 months. Methods-81 toddlers were distributed among three groups according to early type of diet: standard infant formula (SFo, n = 30); long chain polyunsaturated fatty acid (LC-PUFA) enriched formula (LCPFo, n = 26); human milk (HM, n = 25). DQ at 24 months was assessed by Brunet-Lézine's psychomotor devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(90 citation statements)
references
References 12 publications
3
86
0
1
Order By: Relevance
“…The influence of postnatal LCPUFA supply on cognitive function in term infants has been investigated in several supplementation studies (Agostoni et al, 1995(Agostoni et al, , 1997Auestad et al, 2001;Birch et al, 2000;Lucas et al, 1999;Makrides et al, 2000;Scott et al, 1998;Willatts et al, 1998a, b). Some randomized controlled LCPUFA trials in term infants younger than 12 months show a positive influence of dietary LCPUFA on cognitive function, as measured with different methods (Agostoni et al, 1995;Willatts et al, 1998a, b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The influence of postnatal LCPUFA supply on cognitive function in term infants has been investigated in several supplementation studies (Agostoni et al, 1995(Agostoni et al, , 1997Auestad et al, 2001;Birch et al, 2000;Lucas et al, 1999;Makrides et al, 2000;Scott et al, 1998;Willatts et al, 1998a, b). Some randomized controlled LCPUFA trials in term infants younger than 12 months show a positive influence of dietary LCPUFA on cognitive function, as measured with different methods (Agostoni et al, 1995;Willatts et al, 1998a, b).…”
Section: Discussionmentioning
confidence: 99%
“…Only one study reported an influence of LCPUFA in infant nutrition on the Mental Development Index (MDI, Bayley Scales of Infant Development) at 18 months of age (Birch et al, 2000). Other studies at 6 or 12 months (Auestad et al, 2001), 18 months (Lucas et al, 1999) or 24 months of age (Agostoni et al, 1997;Makrides et al, 2000) did not find differences in cognitive function between dietary groups with or without LCPUFA. This summary of the literature suggests that the influence of dietary LCPUFA on cognitive function might be transient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, LC-PUFA of n-3 series influences positively the neurological development of preterm infants, including mental development (Agostoni, 1997;Willatts et al, 1998). It is known that LC-PUFA affects perception and cognitive functions in infancy, although the potential long-term effects in childhood have not been determined.…”
Section: Physiological and Clinical Effects Of Lc-pufa In Infancymentioning
confidence: 99%
“…A small number of studies have examined the association between LC n-3 PUFA intake and visual acuity in infants (34)(35)(36) and reviews in this area support the positive role of LC n-3 PUFA in visual development of infants (37,38) . DHA supplementation has been found to positively affect the mental development of preterm infants (39)(40)(41) and rate of maternal supply of LC n-3 PUFA is thought to be influential in the subsequent cognitive development of the child, although consistent evidence is not available as there have only been a small number of studies. In a comparison of the mental development of children whose mothers were either supplemented with cod liver oil providing 1986 mg EPA + DHA/d or maize oil providing 4747 mg linoleic acid + 83 mg ALA/d from week 18 of pregnancy through to parturition eighty-four children completed a battery of cognitive tests (42) .…”
Section: Cardiovascular Healthmentioning
confidence: 99%